ANALISIS REPRESENTASI IDENTITAS MULTIKULTURAL DALAM DESAIN KOMUNIKASI VISUAL INDONESIA - Yunita, Gesnida; Istianah, Raray; Andiana, Dinda; Firtikasari, Melsya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesia's cultural diversity is frequently used as a visual theme in visual communication design (VCD) products such as posters, packaging, advertisements, and social media content. However, the way multicultural identity is depicted often tends to be symbolic and stereotypical rather than substantive. This study aims to analyze how multicultural identity is represented in Indonesian visual communication design works and to identify the visual patterns and ideological tendencies that emerge within them. This research uses a qualitative descriptive-interpretive method with Roland Barthes' semiotic approach, examining denotative, connotative, and mythological meanings in a purposive sample of visual works published between 2020 and 2025. The data were obtained through visual documentation, literature review, and interviews with practicing designers. The results show that multicultural representation in Indonesian VCD tends to appear in three patterns: ethnic-ornamental representation that emphasizes traditional attributes, religious-symbolic representation that highlights houses of worship and ritual objects, and inclusive-narrative representation that portrays everyday interaction among diverse groups. Ornamental representation dominates commercial works, while inclusive-narrative representation is more common in social campaigns. The study concludes that visual communication design has significant potential to construct an inclusive collective identity, provided that designers move beyond decorative multiculturalism toward contextual and participatory representation involving the communities being depicted.